Sexual dysfunction in men seeking treatment for opioid dependence: a study from India - Venkatesh, Kandappan; Mattoo, Surendra K; Grover, Sandeep (Journal of sexual medicine, 2014)
There is limited literature on opioid dependence patients for the prevalence of sexual dysfunction as assessed by validated questionnaires. To study the prevalence and specified demographic and clinical correlates of sexual dysfunction in men seeking treatment for opioid dependence by using multiple validated instruments. Men with opioid dependence for at least 1 year as per DSM-IV (confirmed by Mini International Neuropsychiatric Interview) (OD group, N=100) and matched healthy controls (HC group, N=50) were evaluated for sexual dysfunction. Arizona Sexual Experience Questionnaire (ASEX), International Index of Erectile Function (IIEF) and Changes in Sexual Functioning Questionnaire Short-Form (CSFQ-14). In men seeking treatment for opioid dependence sexual dysfunction was recorded in 48% by ASEX, and in at least one of the domains in 92% by IIEF and in 90% by CSFQ; in comparison with the healthy controls, the prevalence of sexual dysfunction in patients with opioid dependence was significantly higher by each measure. Compared with healthy controls, sexual dysfunction rates are higher in patients seeking treatment for opioid dependence.